THE INFLUENCE OF WORK EXPERIENCE, WORK MOTIVATION AND WORK CONFLICT ON EMPLOYEE PRODUCTIVITY IN FOOD COMPANIES - Stafrezar, Burhan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the effect of work experience, work motivation and work conflict on employee productivity. The population in this study were employees of the LKS 'A' cake food company in Surabaya with a saturated sampling of 34 employees. Data analysis used the SPSS for Windows version 21 program, with instrument testing, namely validity and reliability tests, classic assumption tests, and hypothesis testing, both partial and simultaneous tests. The results of this study indicate that work experience, work motivation and work conflict have a significant effect both individually and simultaneously on employee work productivity. Work experience is the variable with the most dominant influence. From these findings, organizations and managers are expected to focus on developing skills for their workers in various ways that can improve skills. This includes recognizing employee contributions, communicating company progress and achievements to workers, empowering workers and the knowledge and skills required for optimal performance. Improving all of these factors can improve employee skills and motivation and reduce conflict within the organization leading to increased productivity. This research enriches information/theory regarding the relationship between work experience, work motivation and work conflict on employee productivity.